Genetic Diversity Analysis of Five Different Species of Riccia (Plant Tissue Culture and Biotechnology, 2022)
Five species of the Riccia genus have been investigated by Rapid Amplified Polymorphic DNA (RAPD) analysis. The species is explained and demonstrated with its genetic diversity based on morphological variations. Samples were collected from different parts of the University of Dhaka growing in different habitats around the University campus area. After the study of its morphology, it has been observed that the population of this taxon shows significant variation in plant size, shape, colour, ventral scales, appendages of scales, rhizoids, and the position of male and female receptacles, etc. The RAPD marker system was employed to estimate the genetic diversity within and between the populations based on such morphological variations. Approximately 82% of the variations have been observed within and between genotypes of Riccia as revealed with both phenotypic and genotypic data. The RAPD markers are being used increasingly to analyse the phylogenetic relationship among the liverworts to give the exact framework of taxonomic identification of naturally occurring liverwort Riccia.Plant Tissue Cult. & Biotech. 32(2): 137-144, 2022 (December)